THE MAKING OF CULTURAL VILLAGE IN NAGARI JAWI JAWI, GUNUNG TALANG DISTRICT, SOLOK PROVINCE, WEST SUMATERA - Admiral, Admiral; Yulika, Febri; Citrawati, Anak Agung Istri Agung; Rahmatika, Safara Fitri (Institut Seni Indonesia Padangpanjang, 2019)
Nagari Jawi-Jawi is one area that has a very rich artistic, cultural and literary potential. This is evidenced by the stretching of the activities of cultural arts centers which are held almost every month. To become a developed Cultural Village and tourism destination, there should be attention from the local government, universities, and the private sector to develop its potential. The target to be achieved from the implementation of this program for the people of Nagari Jawi-Jawi, is Services and Training. The approach to help partners, in this case Nagari Jawi Jawi in the effort to be Cultural Village, is conducted in form of counseling and training carried out by the method of lecture and demonstration.